IN-HOSPITAL MORTALITY AMONG PATIENTS WITH ACUTE CORONARY SYNDROME WITH HIGH NEUTROPHIL TO LYMPHOCYTE RATIO - Khan, Sahib; Razaq, Habib Ur; Khan, Abat (Journal of Ayub Medical College Abbottabad, 2021)
Background: High neutrophil to lymphocyte has a great impact on mortality in people with coronary artery disease. Objective of the study was to find out the frequency of in hospital mortality in acute coronary syndrome and high neutrophil to lymphocyte ratio Methods: This study was conducted in cardiology unit, Khyber Teaching Hospital Peshawar from 28th May to 27th November 2019. All patient with ACS and high neutrophil to lymphocytes ratio (NLR >4.7), of age 40-70 years old and both genders were included in the study. All those with infection/sepsis, hematological disorders, previous history of coronary artery diseases, using of immunosuppressed were excluded from the study. Result: Mean age was 55.61±6.65 years, Mean BMI was 25.25±4.32 kg/m2, Male were 130 (70.3%) and female were 55 (40.0%), Diabetes was present in 111 (60.0%) and non-diabetics were 74 (40.0%), Hypertension was present in 122 (65.9%), Smoking history was positive in 81 (43.8%). ‰¤45 years old were 15 (8.1%) and >45 years old were 170 (91.9%). Of BMI ‰¤27.00 were 126 (68.1%) while >27.00 were 59 (31.9%). The mortality rate was 14.6% (27) in hospital. Only diabetes was significant associated with mortality (p value <0.05). The gender, BMI, Hypertension, age and smoking did not show significant difference in mortality (p-value >0.05). Conclusion: There is high rate of in hospital mortality in patient with high neutrophil to lymphocytes ratio. The mortality rate further increases when the patients is diabetics. Further studies are recommended to reject or further strengthen this result.